Expression Regulation of Water Reabsorption Genes and Transcription Factors in the Kidneys of Lepus yarkandensis - Luo, Shengjie; Li, Yongle; Li, Shuwei; Jiang, Renjun; Deng, Fang; Liu, Guoquan; Zhang, Jianping (Frontiers in Physiology, 2022)
Lepus yarkandensis is a desert-dwelling animal that has various adaptations to cope with drought. The kidney maintains water and acid-base balance mainly through the vasopressin-regulated water reabsorption pathway and proximal tubular bicarbonate reabsorption pathway. In this study, we compared the differentially expressed genes (DEGs) and transcription factors in the kidneys of L. yarkandensis and Oryctolagus cuniculus to explore the relationship between the DEGs in kidneys and the animals’ adaptations. Transcriptome sequencing data were used to predict the differentially-expressed water reabsorption genes and their transcription factors. Quantitative real-time PCR, immunohistochemistry, and western blotting were used to detect and verify the expression of DEGs in the kidney at mRNA and protein levels. Transcriptome analysis of the kidney of L. yarkandensis and O. cuniculus showed that 6,610 genes were up-regulated and 5,727 genes down-regulated in data shared by both species. According to the data, 232 transcription factors and their corresponding target genes were predicted, from which genes and transcription factors related to renal water reabsorption were screened. Quantitative RT-PCR results showed AQP1, AQP2, ADCY3, HIF1A, CREB3, and NFATc1 had higher expression in the L. yarkandensis kidney; in comparison, FXYD2 mRNA expression levels were lower. In western blotting, transcription factors HIF1A, NFATc1, NF-κB1, and critical genes ADCY3, ATPA1, and SLC4A4, were highly expressed in the kidneys of L. yarkandensis. Immunohistochemical results showed that the ADCY3 protein was in the basolateral membrane of the collecting duct, the ATP1A1 protein was in the basolateral membrane and medulla of proximal tubules, and the SLC4A4 protein was in the basolateral membrane of proximal tubules. According to these results can be inferred that HIF1A, NFATc1, and NF-κB1 play a certain role in regulating the expression of genes related to water reabsorption in the kidney of L. yarkandensis, thus improving the water reclamation efficiency of L. yarkandensis, so as to adapt to the arid desert environment.